The Role of Teamwork on Employee Job Satisfaction of PT Arita Prima Indonesia Tbk - Nurlaili azzahra , Alya; Santo Hegiarto , Aldy (Universitas Islam Lamongan, 2024)
Human resources (HR) is one of the factors that play an important role as a driver of the organization/company and is a key to the organization/company in carrying out its business activities. The pre-survey results show that the biggest problem lies in the team work and job satisfaction variables. This can be seen by comparing last year at PT Arita Prima Indonesia Tbk on team work with a percentage of 36% in 2023 decreased compared to the previous year.This study aims to determine the role of teamwork on job satisfaction of employees of PT Arita Prima Indonesia Tbk by using descriptive qualitative research methods with the number of informants taken as many as 3 people. the results in this study are the Role of Teamwork on job satisfaction in employees of PT Arita Prima TBK. Good teamwork will lead to job satisfaction such as increased salaries due to target achievement, good relations between leaders and coworkers, increased work to the opportunity to get promoted (promotion).